2001
DOI: 10.1016/s0037-0738(00)00171-8
|View full text |Cite
|
Sign up to set email alerts
|

Astrochronology for the Messinian Sorbas basin (SE Spain) and orbital (precessional) forcing for evaporite cyclicity

Abstract: The Sorbas basin of SE Spain contains one of the most complete sedimentary successions of the Mediterranean re¯ecting the increasing salinity during the Messinian salinity crisis. A detailed cyclostratigraphic study of these successions allows a correlation of the sedimentary cycle patterns to astronomical target curves. Here, we present an astrochronological framework for the Messinian of the central part of the Sorbas basin. This framework will form a solid basis for high-resolution correlations to the margi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
166
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(179 citation statements)
references
References 40 publications
13
166
0
Order By: Relevance
“…Meanwhile, integrated stratigraphic research in the Sorbas basin (Sierro et al, 1999;Krijgsman et al, 1999aKrijgsman et al, , 2000 has revealed: (1) that the top of the Abad marls has exactly the same astrochronometric age as pre-evaporite successions elsewhere in the Mediterranean; (2) that the Yesares Gypsum contains 14 and the conformably overlying Sorbas unit 3 cycles ( 17 cycles); (3) that the Zorreras contains 8 cycles with caspi-brackish ostracode fauna's in the two distinct whitish limestone beds and (4) that all these units possess a reversed polarity. In our opinion, the conspicuous-integrated stratigraphic-similarities with the classical Mediterranean succession cannot be interpreted other than that the Sorbas basinal succession reflects essentially the same depositional history as other Mediterranean basins during the Messinian.…”
Section: Results From Integrated Stratigraphymentioning
confidence: 99%
“…Meanwhile, integrated stratigraphic research in the Sorbas basin (Sierro et al, 1999;Krijgsman et al, 1999aKrijgsman et al, , 2000 has revealed: (1) that the top of the Abad marls has exactly the same astrochronometric age as pre-evaporite successions elsewhere in the Mediterranean; (2) that the Yesares Gypsum contains 14 and the conformably overlying Sorbas unit 3 cycles ( 17 cycles); (3) that the Zorreras contains 8 cycles with caspi-brackish ostracode fauna's in the two distinct whitish limestone beds and (4) that all these units possess a reversed polarity. In our opinion, the conspicuous-integrated stratigraphic-similarities with the classical Mediterranean succession cannot be interpreted other than that the Sorbas basinal succession reflects essentially the same depositional history as other Mediterranean basins during the Messinian.…”
Section: Results From Integrated Stratigraphymentioning
confidence: 99%
“…This is carried out in the upper 13 ocean levels of the model, 0 to 1 km depth, which is an appropriate palaeobathymetry in the model for either side of the Messinian MediterraneanAtlantic seaways (e.g. van Assen et al, 2006;Fortuin and Krijgsman, 2003;Hilgen et al, 2000;Hodell et al, 1994;Krijgsman, 2001;Krijgsman et al, 2004;van der Laan et al, 2006). Although the continental seaways were probably not this deep, or at least not for the entire Messinian, because of the model's horizontal resolution constraints, the parameterisation also necessarily captures part of the mixing and flow that occurs above the continental shelf in the Gulf of Cadiz (Atlantic) and the Alboran Sea (Mediterranean).…”
Section: Mediterranean-atlantic Exchangementioning
confidence: 99%
“…If true, the authors point out that the boundary would not coincide with a major deglaciation event and associated glacio-eustatic sea-level rise as generally believed; tectonics, rather, are thought to have played a significant role. Earlier, Krijgsman et al (2001) have shown that the initiation of the Messinian Salinity Crisis at -6 Ma was not related to a glacio-eustatic event either.…”
Section: Status Of the Hierarchical Subdivision Of Higher Order Marinmentioning
confidence: 96%